GRACE leakage error correction with regularization technique: case studies in Greenland and Antarctica. Issue 3 (4th January 2017) - Mu, Dapeng; Yan, Haoming; Feng, Wei; Peng, Peng
Summary: Filtering is a necessary step in the Gravity Recovery and Climate Experiment (GRACE) data processing, but leads to signal leakage and attenuation obviously, and adversely affects the quality of global and regional mass change estimates. We propose to use the Tikhonov regularization technique with the L-curve method to solve a correction equation which can reduce the leakage error caused by filter involved in GRACE data processing. We first demonstrate that the leakage error caused by the Gaussian filter can be well corrected by our regularization technique with simulation studies in Greenland and Antarctica. Furthermore, our regularization technique can restore the spatial distribution of original mass changes. For example, after applying the regularization method to GRAEC data (2003–2012), we find that GRACE mass changes tend to move from interior to coastal area in Greenland, which are consistent with recent other studies. After being corrected for glacial isostatic adjustment effect, our results show that the ice mass loss rates were 274 ± 30 and 107 ± 34 Gt yr −1 in Greenland and Antarctica from 2003 to 2012, respectively. And a 10 ± 4 Gt yr −1 increase rate in Greenland interior is also detected.